Subspace–hypercyclic weighted shifts - Bamerni, Nareen; Kılıçman, Adem (Element D.O.O.admin@ele-math.com, 2018)
Our aim in this paper is to obtain necessary and sufficient conditions for bilateral and unilateral weighted shift operators to be subspace-transitive. We show that the Herrero question [6] holds true even on a subspace of a Hilbert space, i.e. there exists an operator T such that both T and T∗ are subspace-hypercyclic operators for some subspaces. We display the conditions on the direct sum of two invertible bilateral forward weighted shift operators to be subspace-hypercyclic.